Somatic influences on subjective well-being and affective disorders: the convergence of thermosensory and central serotonergic systems - Raison, Charles L.; Hale, Matthew W.; Williams, Lawrence; Wager, Tor D.; Lowry, Christopher A. (Frontiers in Psychology, 2015)
Current theories suggest that the brain is the sole source of mental illness. However, affective disorders, and major depressive disorder (MDD) in particular, may be better conceptualized as brain-body disorders that involve peripheral systems as well. This perspective emphasizes the embodied, multifaceted physiology of well-being, and suggests that afferent signals from the body may contribute to cognitive and emotional states. In this review, we focus on evidence from preclinical and clinical studies suggesting that afferent thermosensory signals contribute to well-being and depression. Although thermoregulatory systems have traditionally been conceptualized as serving primarily homeostatic functions, increasing evidence suggests neural pathways responsible for regulating body temperature may be linked more closely with emotional states than previously recognized, an affective warmth hypothesis. Human studies indicate that increasing physical warmth activates brain circuits associated with cognitive and affective functions, promotes interpersonal warmth and prosocial behaviour, and has antidepressant effects. Consistent with these effects, preclinical studies in rodents demonstrate that physical warmth activates brain serotonergic neurons implicated in antidepressant-like effects. Together, these studies suggest that 1) thermosensory pathways interact with brain systems that control affective function, 2) these pathways are dysregulated in affective disorders, and 3) activating warm thermosensory pathways promotes a sense of well-being and has therapeutic potential in the treatment of affective disorders.